2018
DOI: 10.9771/rc-ufba.v12i3.26177
|View full text |Cite
|
Sign up to set email alerts
|

Práticas Acadêmicas Conflitantes com os Padrões Éticos e seus Reflexos na Conduta do Futuro Profissional Contábil

Abstract: <p>Com um mercado cada vez mais competitivo que busca profissionais qualificados e com discernimento ético, precisa-se constantemente renovar a discussão sobre ética no meio acadêmico. Nesse contexto, realizou-se este estudo com o propósito de analisar a percepção dos acadêmicos do curso de<strong> </strong>Ciências Contábeis de uma Instituição de Ensino Superior, quanto à adoção de práticas acadêmicas conflitantes com os padrões éticos e seus reflexos na conduta do futuro profissional da con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
4
0
4
Order By: Relevance
“…Several studies have already been carried out on dishonesty in the academic environment: Oliveira, Assis, Silva and Oliveira Neto (2014) verified that there are no significant differences between the perception of dishonesty by students and professors; however, those who thought that they would be more severe with dishonest ones, and who also judged to be more rigorous with those who commit dishonesty. Viana et al (2018) found that most students agree that dishonest practices can influence the ethical behavior of future accounting professionals, but 44.38% of students do not identify a possible correlation between ethics in college and the profession.…”
Section: Theoretical Referencementioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have already been carried out on dishonesty in the academic environment: Oliveira, Assis, Silva and Oliveira Neto (2014) verified that there are no significant differences between the perception of dishonesty by students and professors; however, those who thought that they would be more severe with dishonest ones, and who also judged to be more rigorous with those who commit dishonesty. Viana et al (2018) found that most students agree that dishonest practices can influence the ethical behavior of future accounting professionals, but 44.38% of students do not identify a possible correlation between ethics in college and the profession.…”
Section: Theoretical Referencementioning
confidence: 94%
“…Regarding academic dishonesty, research has already been carried out on the perception of justice (Resh & Sabbagh, 2017;Santos, Avelino, Cunha & Colauto, 2020); the relationship with cynicism (Nasu & Afonso, 2020); reflections on professional conduct (Viana, Santos, Rodrigues, Lima & Viana, 2018), among others. Also in this area, but seeking to understand the motivations of students' dishonesty, other studies were carried out about obtaining better grades and not disappointing parents (McCabe, Treviño & Butterfiled, 1999;Quaye, 2010); the student-teacher relationship (Zelna & Bresciani, 2004;Starovoytova & Namango, 2016); and on plagiarism (Ives et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Discussions about the effects of dishonest practices are representative for they are a likely precursor to one engaging in unethical behavior at work and, therefore, a threat to a professional's career success and a risk as to organizational ethical violations (Winrow, 2016;Nguyen & Tran, 2018). Thus, dishonesty in academia is the focus of study in the higher education environment, as it is understood that today's students will be tomorrow's professionals (Stone et al, 2009;Taniguchi et al Sanchez, Cappellozza & Filenga, 2011;Sanchez & Innarell, 2012;Winrow, 2016;Viana, Rodrigues, Lima & Viana, 2018), and the medium in which an individual is inserted can influence their behavior. In this sense, the Theory of Planned Behavior (TPB) measures the propensity to a behavior based on the intention of the human being, that is, how much effort an individual is willing to make in favor of an action (Ajzen, 1991).…”
Section: Cheating In the Academic Environmentmentioning
confidence: 99%
“…Competitiveness in the labor market triggers a demand for qualified professionals with ethical discernment (Viana, Santos Rodrigues, Lima & Viana, 2018). Moreover, the globalized world has created a more integrated and borderless environment, stimulating new debates in the business area, especially on ethical attitudes.…”
Section: Ethics In the Work Environmentmentioning
confidence: 99%
“…A respeito da desonestidade acadêmica, já foram desenvolvidas pesquisas acerca da percepção de justiça (Resh & Sabbagh, 2017;Santos, Avelino, Cunha & Colauto, 2020); da relação com o cinismo (Nasu & Afonso, 2020); reflexos na conduta profissional (Viana, Santos, Rodrigues, Lima & Viana, 2018), entre outros. Também nessa ceara, mas buscando compreender as motivações da desonestidade dos estudantes, outras pesquisas foram elaboradas acerca da obtenção de melhores notas e não decepcionar os pais (McCabe, Treviño & Butterfiled, 1999;Quaye, 2010); o relacionamento entre aluno-professor (Zelna & Bresciani, 2004;Starovoytova & Namango, 2016); e sobre plágio (Ives et al, 2016).…”
Section: Introductionunclassified